How do you solve using the completing the square method x^2+6x=7?

1 Answer
Apr 18, 2016

Create a perfect square trinomial on the left side, and your solution is not far away!

Explanation:

First, the lead coefficient should = 1 to make this easiest.
Then, take half of the linear coefficient, then square it. Add to both sides:
x^2+6x+9=7+9
Factor the left:
(x+3)^2=16
Take the square root of both sides:
sqrt((x+3)^2)=sqrt(16)
Left side inverse operations undo each other, on the right side, don't forget the +- on the right!

x+3=+-4

so x + 3 = 4 or x + 3 = -4

so x = 1 or -7.